Dependence of Green’s function of an $e$-dichotomous differential equation with matrix projector in the space M on parameters - Teplinsky, Yu. V. (Ukrains’kyi Matematychnyi Zhurnal, 1994)
In the space $\mathfrak{M}$ of bounded numeric sequences, we consider dichotomonly differential equation with a matrix projector. We prove that Green's function of this equation exists, and give the conditions, under which it is continuous and differentiable with respect to the parameters in the equation.